Algorithm-based Verification of Manufacturing Constraints for a Loadpath Reinforced Fabric - Gebhardt, Philipp; Bätge, Tjard; Türck, Eiko; Vietor, Thomas (Procedia CIRP, 2019)
Lightweight construction has become increasingly important in recent decades. The fundamental idea of lightweight design is not to save weight at any price, but to use resources responsibly. Less waste and the right material in the right place can save costs and reduce energy consumption. Lightweight construction often increases design complexity. Algorithms can help to solve highly complicated design tasks effectively. This paper shows how load paths can be used to reinforce a component optimally. The load path method is an efficient way of structural reinforcement. It also fits perfectly to a new manufacturing method which will be shortly discussed: A textile machine for biaxial NCF (non crimp fabrics) with a special unit for offsetting warps of carbon fibers. This novel technology allows the reinforcing material to be placed at exactly the right place at high production speeds. The base material can be a cheaper fiber, such as glass fiber, the local reinforcement material can be a high performance fiber, such as carbon fiber. The manufacturing process is only considered to the extent that all relevant manufacturing restrictions can be extracted. Five key restrictions are being studied (e.g. minimal curvature radius or minimal and maximal stacking angle). All restriction can be broken down to geometrical information and formulated as various mathematical problems. These problems can be solved efficiently by known algorithms.